(untitled) (International Journal of Medical and Surgical Sciences, 2014)
Nanotechnology is generating a strong impact in preclinical and clinical drug development. The diversity of current nanotechnologies offers a broad platform used to enhance the performance of drug discovery screening, to develop sensitive and specific methods used to unveil the mechanisms behind the actions of drugs, to determine the function and interaction between molecules, and to study the physiological and pathological changes of cellular components. In addition, advancements in nanobiotechnology have led to the design of new nanomaterial-based drug candidates that present a novel approach to medical diagnostics and therapeutics. The biocompatible nanoarchitecture of the marketed nanocarriers used for drug delivery has increased the solubility and effectiveness of classical drugs, and has provided the technology required for the targeted delivery of encapsulated tissue-organ specific therapeutics. Because of its effect on drug development, nanotechnology serves as the foundation for many future medical endeavors. This article provides an overview of the basics of nanobiotechnology, and discusses its applications in drug discovery, design, and delivery systems.